2021
DOI: 10.3390/dairy2020020
|View full text |Cite
|
Sign up to set email alerts
|

Leptospira interrogans Serovar Hardjo Seroprevalence and Farming Practices on Small-Scale Dairy Farms in North Eastern India; Insights Gained from a Cross-Sectional Study

Abstract: Leptospirosis is a zoonotic disease of major public health concern in India. Bovines play an important role in maintaining and transmitting this disease and proximity between dairy cows and humans makes the dairy cow-human nexus a transmission route of public health interest, yet one currently under-examined in North Eastern India. We report a cross-sectional survey carried out on small-scale dairy farms in the states of Assam and Bihar in North Eastern India investigating seroprevalence for Leptospira interro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
(60 reference statements)
1
3
0
Order By: Relevance
“…The present study demonstrated age and health status of the animal were risk factors significantly associated with the occurrence of leptospirosis. Our finding in respect to the age-wise prevalence was in agreement with earlier studies and Leahy et al (2021), who reported more seropositivity in older cattle. However, Dogonyaro et al (2020) found no significant association among the different age groups with bovine leptospirosis in South Africa.…”
Section: Advances In Animal and Veterinary Sciences Discussionsupporting
confidence: 93%
“…The present study demonstrated age and health status of the animal were risk factors significantly associated with the occurrence of leptospirosis. Our finding in respect to the age-wise prevalence was in agreement with earlier studies and Leahy et al (2021), who reported more seropositivity in older cattle. However, Dogonyaro et al (2020) found no significant association among the different age groups with bovine leptospirosis in South Africa.…”
Section: Advances In Animal and Veterinary Sciences Discussionsupporting
confidence: 93%
“…Alternatively, lower prevalences have been reported in some countries, it was 3% in North Eastern India 40 , 3.2% in Poland 41 , 13% in Tanzania 42 , 20.3% in Sri Lanka 43 , 31.3% in Brazil 44 , and 24.48% in southwestern Ethiopia 45 .…”
Section: Discussionmentioning
confidence: 91%
“…and Leptospira spp. infection in urban/peri-urban areas than rural areas in Bihar and Assam [ 29 , 30 , 31 ]; these infections are considered as the main cause of the five selected reproductive problems [ 15 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…seroprevalence at herd level in Assam was 16.5% in contrast to 0.3% in Bihar [ 15 ], while herd level C. burnetii seroprevalence in Assam was 5.8% in contrast to 27.1% in Bihar and Leptospira spp. seroprevalence in Assam was 1.2% in comparison to 4.5% in Bihar [ 31 , 34 ]. All three infectious agents may cause reproductive problems with a similar presentation in dairy animals [ 43 , 53 , 54 ] and therefore it may not be wise to estimate the economic cost based on investigation of one infectious agent (say brucellosis).…”
Section: Discussionmentioning
confidence: 99%